Indoor air quality at bus terminal and their influence on health / Aaina Afrina Abdul Manaf... [et. al] - Abdul Manaf, Aaina Afrina; Hashim, Nur Ashikin; Mohd Isa, Nurul Athira (2019)
Over the most recent couples of decades, indoor air quality (IAQ) has gotten expanding consideration from the community. The quality of indoor air has a significant bad impact on human health. According to the previous studies, it has been evaluated that most individuals do invest about 90% of the energy staying indoor. A building's management department is usually responsible for improving the quality of the indoor environment by providing good service and boosting productivity and satisfaction for the building’s occupants. Thus, a salient point of this study is to determine the indoor air quality at Terminal Bersepadu Selatan Kuala Lumpur and their influence on health. The objectives of the study are (i) to determine the concentration on indoor air pollutants (CO, CO2, and NO2 ) during weekdays and weekends, (ii) to identify the concentration of particulate matter PM10 and PM2.5 during weekdays and weekends, (iii) to measure the concentration of heavy metals (Pb, Mg, Fe, and Cd) in the particulate matter collected between weekdays and weekends and (iv) to determine the association between indoor air quality parameters and sick building syndrome. For these reasons, monitoring of air quality was carried out using Environmental Monitoring Equipment EVM-7 to identify levels of CO, CO2 , NO2 , and PM10 while PM2.5 was measured using DustTrak II Aerosol Monitor Model 8520. The particulate matter was collected using an air sampling pump GilAir5. 40 workers in the departure hall were randomly selected for the health survey during the monitoring period, using questionnaire to identify the SBS. The result showed that weekends have a higher reading compared to weekdays; the concentration level of CO, CO2 and NO2 was below the corresponding American Conference of Governmental Industrial Hygienists' (ACGIH) standards under normal operating conditions. Next, the concentration level of particulate matter PM10 and PM2.5 complies with a permissible limit of 150µg/m³ by Industrial Code of Practice on Indoor Air Quality 2010. Therefore, in this study, all the indoor air quality parameters are compiled to the required permissible limit. However, the terminal bus workers still do experience sick building syndrome such as headache and cough. Thus, there is an association between indoor air quality parameters and the sick building syndrome among the bus terminal workers.